Influence of Thinking Ability About Discussion Method for Student Learning Achievement in PAI Lesson in SMP Negeri 18 Surabaya - Mus tofa; Mahsun Jayadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Formulation of the problem of this research the researcher described as follows; 1. How is the application of learning strategies to improve the ability to think with the method of discussion in SMP Negeri 18 Surabaya ?; 2. How are student achievement in PAI subjects at SMP Negeri 18 Surabaya ?; 3. How does the effect of the application of learning strategies to increase the ability to think with the method of discussion on student achievement in the PAI (Islamic Religious Education )lesson at SMP Negeri 18 Surabaya? This research approach was a quantitative approach, the research population was all 7th grade students of SMPN 18 Surabaya, and the sample was 15% of the population, namely 45 students; Methods: observation, interview, documentation, and questionnaire, while analyzing the data using the statistical formula.